Pengembangan LKPD Berbasis Discovery Learning untuk Memfasilitasi Kemampuan Pemahaman Matematis Siswa SMP Pada Materi Himpunan - Prayulia Trisandi, Yogi; Kartini; Saragih, Sehatta (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This research is motivated by the low mathematical comprehension abilities of students. One effort to facilitate mathematical comprehension abilities is by developing teaching materials in the form of Student Worksheets (LKPD) using the discovery learning model. This study aims to produce valid and practical LKPD products to facilitate students' mathematical comprehension abilities. The form of this research is development research using the 4-D model (define, design, develop, and disseminate). The research subjects are 9 seventh-grade students from SMP Yabri Terpadu Pekanbaru. The research instruments consist of interviews, validation sheets, and student response sheets. Data analysis techniques involved analyzing the validation results and student response data. The results of the data analysis showed that the LKPD met the validity criteria with an average percentage of 87.52%, categorized as highly valid, and also met the practicality criteria with an average percentage of 84.19%, categorized as highly practical. Based on the data analysis results, it is concluded that the developed LKPD meets the validity and practicality criteria, thus can be used in mathematics learning.